Pembinaan kepada Para Tentor Asrama Bahasa Ponpes Sunan Drajat tentang Pengaplikasian Metode Pair Work untuk Meningkatkan Keaktifan Speaking Para Santri - Shobaha, Shohiyah; Lahita, Nanda (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
Sunan Drajat Islamic Boarding School is one of the famous Islamic boarding schools located in Lamongan district. As an Islamic boarding school that has thousands of students, Pondok Pesantren Sunan Drajat continues to strive to improve the quality of the students. Various activities are carried out to produce quality and competitive Islamic boarding school graduates. One of the superior programs at the Sunan Drajat Islamic Boarding School is the provision of an English language dormitory to support students in improving their foreign language skills. In the process of implementing English language learning activities for students, tutors often face various problems. One of the problems that often occurs is that students often appear unenthusiastic and less active in practicing speaking during the classroom learning process. This causes confusion among tutors about what methods are effective to apply in order to make all students in the class more active to speak English. With the aim of providing a reference to the tutors regarding a method that can be applied to encourage students to actively speak in class as a form of problem solving, coaching was held for the tutors regarding the application of teaching methods whose effectiveness has been proven for speaking skill in many previous studies, namely